2003
DOI: 10.1152/japplphysiol.00303.2003
|View full text |Cite
|
Sign up to set email alerts
|

Independent cerebral vasoconstrictive effects of hyperoxia and accompanying arterial hypocapnia at 1 ATA

Abstract: Breathing 100% O2 at 1 atmosphere absolute (ATA) is known to be associated with a decrease in cerebral blood flow (CBF). It is also accompanied by a fall in arterial Pco2 leading to uncertainty as to whether the cerebral vasoconstriction is totally or only in part caused by arterial hypocapnia. We tested the hypothesis that the increase in arterial Po2 while O2 was breathed at 1.0 ATA decreases CBF independently of a concurrent fall in arterial Pco2. CBF was measured in seven healthy men aged 21-62 yr by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(197 citation statements)
references
References 58 publications
(71 reference statements)
8
183
3
3
Order By: Relevance
“…Although hypoxia can increase CBF, experimental hyperoxia showed a small trend toward CBF decrease. 52,53 There was no statistically significant group difference in measures of ABG percent oxygen saturation in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…Although hypoxia can increase CBF, experimental hyperoxia showed a small trend toward CBF decrease. 52,53 There was no statistically significant group difference in measures of ABG percent oxygen saturation in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…We therefore added CO 2 to partially offset this side effect. Similar strategies have been used in previous reports in the literature (see also Discussion) (Floyd et al, 2003).…”
Section: Oxygen Modulationmentioning
confidence: 80%
“…Under hyperoxia or hypoxia conditions, the relationship between CMRO 2 /CBF and CO 2 may be different (i.e., there could be an interaction term between O 2 and CO 2 effects). There is some evidence suggesting that the interaction term is negligible for CBF (Floyd et al, 2003). However, future studies are needed to examine the interaction effect on CMRO 2 .…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Floyd et al 16 have shown that the decrease in CBF while breathing 100% O 2 is attributable to the combination of arterial hyperoxia and hypocapnia and that hyperoxia causes a cerebral vasoconstriction independent of the vasoconstriction associated with arterial hypocapnia. The decrease in ICP and flow velocity is probably due to the vasoconstricting effects of hyperoxia, and a small decrease in ETCO 2 is caused by breathing 100% O 2 .…”
Section: Hyperoxiamentioning
confidence: 99%